Day 2 Thu, February 27, 2014 2014
DOI: 10.2118/168171-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of a Differentiated Chelant-Based Hydrofluoric Acid for the Removal of Aluminosilicates, Fines, and Scale in Offshore Reservoirs of the Gulf of Mexico

Abstract: The Ewing Bank 873 (EW 873) Field is an offshore mature field in the Gulf of Mexico that produces hydrocarbon from Pliocene stacked turbidite sands. Wells in the EW 873 Field have experienced production impairment from formation damage, such as aluminosilicates, fines, and scale, including calcium carbonate (CaCO3) and barium sulfate (BaSO4). This paper discusses the results of the successful application of a differentiated chelant-based hydrofluoric (HF) acid to remove formation damage and enhance oil product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To lower the corrosion rate, a corrosion inhibitor (sulfur-based) was included in the fluid at a concentration of 2 and 4% (Tests 3 and 4), which now has a pH of 2.5 and a concentration of 0.6 M GLDA. The reason for this change in pH and chelant concentration is because this is within the operating condition of the GLDA/HF* or other APCA/HF fluid, based on this work and other publications (Mahmoud et al 2011 andReyes et al 2013b;Sopngwi et al 2014). The corrosion rate, after including the inhibitor, decreased to 0.162 and 0.142 lbm/ft 2 for a 6-hour exposure period at 360°F.…”
Section: Discussionmentioning
confidence: 54%
“…To lower the corrosion rate, a corrosion inhibitor (sulfur-based) was included in the fluid at a concentration of 2 and 4% (Tests 3 and 4), which now has a pH of 2.5 and a concentration of 0.6 M GLDA. The reason for this change in pH and chelant concentration is because this is within the operating condition of the GLDA/HF* or other APCA/HF fluid, based on this work and other publications (Mahmoud et al 2011 andReyes et al 2013b;Sopngwi et al 2014). The corrosion rate, after including the inhibitor, decreased to 0.162 and 0.142 lbm/ft 2 for a 6-hour exposure period at 360°F.…”
Section: Discussionmentioning
confidence: 54%
“…1) suggested that the solids contained BaSO 4 scale as the bailedout samples were soluble in concentrated sulfuric acid and insoluble in xylene, warm water, 15% hydrochloric acid (HCl), and also in 10% sodium hydroxide (NaOH). Furthermore, as stated by Sopngwi et al (2014), X-ray diffraction (XRD) analyses of the solids indicated a high presence of BaSO 4 scale as the bailed-out samples contained 90% BaSO 4 . As mentioned earlier, it is important to note that the BaSO 4 tubular scale was concluded to have been caused by incompatible mixing between the barium-rich formation water and sulfate-rich biocide inhibited seawater that broke through from an offset injection well (Table 3).…”
Section: Identification Of the Baso 4 Tubular Scalementioning
confidence: 77%
“…Additionally, with NWB formation damage and production impairment already established to be a problem on the well, the intervention created an opportunity to effectively conduct a chelant-based HF acid treatment that increased oil production by as much as 305% on the well (Sopngwi et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations